2022
DOI: 10.3390/biology11060829
|View full text |Cite
|
Sign up to set email alerts
|

Predator-Prey Relationship between Urban Bats and Insects Impacted by Both Artificial Light at Night and Spatial Clutter

Abstract: Predators respond to the increase of prey by aggregation in space or foraging more often. However, foraging habitat suitability limits predators’ responses. For nocturnal insectivorous bats, artificial light at night (ALAN) can trigger insect prey aggregation. It is not clear how ALAN might affect predator-prey relationships in the urban setting, where urban bats could have adapted to the city, and novel spatial complexity introduced by man-made objects might alter foraging habitat suitability. We strategicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…Besides, Travis Longcore and Catherine Rich reported a high mortality rate of migratory birds on the elevated and lighted building structures triggered by the lost nighttime visibility due to ALAN's induced sky glow ( 65 , 78 ). Seasonal migrating or nomadic birds rely on the natural signals of the appropriately scheduled earthly seasons.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, Travis Longcore and Catherine Rich reported a high mortality rate of migratory birds on the elevated and lighted building structures triggered by the lost nighttime visibility due to ALAN's induced sky glow ( 65 , 78 ). Seasonal migrating or nomadic birds rely on the natural signals of the appropriately scheduled earthly seasons.…”
Section: Resultsmentioning
confidence: 99%
“…Difficulty foraging in areas with urban clutter (e.g. fences and buildings), which prevented large-sized bats from foraging under ALAN (Li and Wilkins 2022 ), could also explain this pattern for nighthawks. Our simulations showed that our model had limited power to detect a positive main effect of urban land cover when we used the fitted coefficient value (+ 0.83).…”
Section: Discussionmentioning
confidence: 99%
“…In a study focusing on urban bats that might have somewhat adapted to ALAN in the city, scientists found that the big brown bat, eastern red bat, and silver-haired bat showed higher levels of activity at brighter sites in response to increased insect availability (Li, Wilkins, 2022). However, their activity was still limited by the spatial clutter, which affected foraging habitat suitability (Li, Wilkins, 2022).…”
Section: Discussionmentioning
confidence: 99%